EFFECTIVENESS OF “RESAM KAMPUNG” IN NATURAL RESOURCE MANAGEMENT IN GAYO LUES REGENCY ACEH PROVINCE – INDONESIA - Ruhaya Ruhaya; Yanis Rinaldi; Ichwana Ramli (Universitas Syiah Kuala, 2023)
Local wisdom that regulates life to maintain the balance of natural resources and supports ecological wisdom is essential in Gayo Lues Regency, Aceh Province. This local wisdom has been implemented from generation to generation as village regulation known resam kampung. The article investigates the effectiveness of the implementation of resam kampung in the management of natural resources, specifically for water source areas in Gayo Lues Regency, by choosing three villages, i.e Sangir, Agusen and Rerebe, in Gayo Lues Regency. This article utilises a qualitative descriptive analysis method through interviews and FGD (focus group discussions), and data analyzed using the scoring method to obtain an effectiveness value of legal factor indicators based on Soerdjono Soekanto's legal theory, i.e. legal factors, law enforcement factors, facilities factors, community factors and cultural factors. Resam kampung is effectively applied for natural resource management based on the value of the legal factor especially in the management of water resources area. The application of rules with local cultural values and wisdom coupled with the guidance and cooperation of agencies related to forest and natural resource supervision is important to sustain natural resource management under the reusam kampung in future.